Bedaquiline and linezolid regimens for multidrug-resistant tuberculosis: a systematic review and meta-analysis - Mahdis Cheraghi; Mehrnaz Amiri; Sahar Andarzgoo; Fatemeh Zarei; Zahra Sadat Seghatoleslami; Rosella Centis; Dina Visca; Lia D’Ambrosio; Emanuele Pontali; Mohammad Javad Nasiri; Giovanni Battista Migliori (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: Multidrug-resistant tuberculosis (MDR-TB) remains a global public health challenge, complicating treatment strategies and requiring advanced therapeutic approaches. The persistence of MDR-TB has led to a demand for regimens that are more effective in improving treatment outcomes and controlling transmission. This systematic review and meta-analysis sought to examine the efficacy of linezolid (LZD) and bedaquiline (BDQ) in MDR-TB treatment regimens, evaluating their roles in enhancing therapeutic success and informing optimized management of MDR-TB. Methods: A comprehensive search was conducted across MEDLINE (PubMed), EMBASE, the Cochrane Central Register of Controlled Trials, Scopus, and Web of Science for randomized controlled trials assessing the efficacy of LZD and BDQ in MDR-TB patients up to September 14, 2024. We analyzed treatment outcomes, reporting favorable outcomes (cured and treatment completed) and unfavorable outcomes (death, treatment failure, and loss to follow-up) with a 95% confidence interval. Results: Our analysis included 11 trials, with a total of 1,999 participants. The findings indicate that BDQ+LZD-containing regimens yield significantly higher favorable treatment outcomes (84.5%; 95% CI, 79.8%-88.2%) and lower unfavorable outcomes (15.4%; 95% CI, 11.6%-20.2%). In contrast, regimens lacking either LZD or BDQ show lower efficacy, with favorable outcomes at 66.8% (95% CI, 59.5%-73.4%) and unfavorable outcomes at 33.0% (95% CI, 25.6%-41.4%). Conclusions: MDR-TB treatment regimens including BDQ and LZD lead to significantly better patient outcomes. The combined bactericidal and protein synthesis-inhibiting effects of BDQ and LZD create a powerful therapeutic synergy. Adding pretomanid further enhances this effectiveness, highlighting its value in complex cases. Future research should focus on optimizing these regimens for safety and efficacy and explore adjunctive therapies to improve MDR-TB outcomes even further.